LEVEL OF PATIENT SATISFACTION WITH REFERRAL PROGRAM (PRB) ON THE QUALITY OF PRESCRIPTION SERVICES FROM TWO BRANCHES OF KIMIA FARMA PHARMACY IN BENGKULU CITY - Dewi Winni Fauziah; Dinna Fransiska Putri; Aina Fatkhil Haque; Elly Mulyani (Jurnal Farmasi Malahayati, 2023)
The quality of health services is a factor that must be considered by a health service facility, especially after the implementation of the health insurance program. The quality of service can be judged by the level of patient satisfaction with the by diameters of reliability, responsiveness, ability and empathy. The results of the satisfaction assessment can be one of the evaluation materials in an effort to improve service quality. The research was conducted at Apotek Kimia Farma 72 and Apotek Kimia Farma 220 Bengkulu City. This type of research is a descriptive observational study with a quantitative approach. How to take samplesÂ  with the non-probability sampling method with accidental sampling techniques. The sample in this study were 95 respondents. This study was analyzed descriptively based on the Likert scale, by measuring the question indicators of reliability, responsiveness, assurance and empathy. The results showed the percentage of PRB patient satisfaction level with prescription servers at Apotek Kimia Farma 72 was 82.54% in the reliability dimension with the classification was very satisfied, the responsiveness dimension was 82.72% with the classification of very satisfied, the ability dimension was 83.36% with the classification very satisfied and the empathy dimension was 83.27% with a very satisfied classification. Whereas for Apotek Kimia Farma 220, a percentage of 82.75% was obtained on the reliability dimension with the classification very satisfied, the responsiveness dimension was 83.5% with the classification very satisfied, the ability dimension was 82.13% with the classification very satisfied and the empathy dimension was 84.38% with a very satisfied classification. These results show that the percentage of satisfaction at Apotek Kimia Farma 220 is higher than Apotek Kimia Farma 72.Keywords: Pharmacy, Patients Satisfaction Level, Prescription Services, Kimia Farma, Pharmaceutical services